The plan of land use decentralised participatory tool between legal text and reality - case of the land use plan for the new urban residential area (NURA01) of the city of M'sila - Algeria - Benlatreche Abdelmadjid; FeloussiaLahcene (My University, 2022)
The land use plan is one of the new reconstruction tools through which the Algerian State seeks to distribute roles between the central authority and the local community represented by the governorate and the municipality, respectively. The decentralization and the participation when preparing the land use plan help strengthen the dialogue between the state and population representatives, facilitate the decision-making and improve the management of local affairs, As a result, projects that elevate and meet the society requirements are of a higher efficiency. In this perspective, this research aims at identifying the indicators of decentralization and participation at the stage of preparation of the land use plan, and monitoring them in real based on a descriptive analytical approach. The results of this study demonstrated that there is unilateralism in the preparation of the land use plan through the existence of a prior intention from Municipality and of M'sila to impose their vision, while other Institutions are neglected
Keywords: The land use plan, decentralization, participatory, public investigation, The audience